Care in thermorregulation of the preterm infant: the nurse’s view - Rolim, Karla Maria Carneiro; Araújo, Ana Flávia Pessoa Correia; Campos, Naylê Maria Moreira; Lopes, Simone Miranda Barbosa; Gurgel, Eloah de Paula Pessoa; Campos, Antônia do Carmo Soares (Rev Rene, 2010)
This is an exploratory descriptive study with qualitative approach which was carried out in the Neonatal Intensive Care Unit (NICU) of the Teaching Maternity Assis Chateaubriand in Fortaleza-CE from November 2008 to February 2009, with the objective of knowing the nurse’s perception regarding the nursing care in the thermoregulation of preterm infants in NICU. A semi-structured interview was carried out, containing identification data and subjects concerning the nursing assistance to preterm infants in thermoregulation. The data were analyzed according to the pertinent literature of the theme, being presented in text discussions. The temperature control is a task that requires attention of the entire team. We recommend more qualification and sensitization of the nursing team through permanent education, having as goals the assistance optimization and attention to the life quality of the hospitalized baby. We verified the importance of maintaining the appropriate heating to the baby, once the thermoregulation is a fundamental aspect of neonatal attention.